Where will this shoe take you? : a walk through the history of footwear [book review] - Evensen, Nancy C. (1997)
Lawlor, Laurie. Where Will This Shoe Take You? A Walk Through the History of Footwear. Walker, 1996. ISBN 0-8027-8434-8. $17.95. 132 pp. A+ 4-6 NF Reviewed by Nancy C. Evensen The shoes people create and wear tell stories about themûhow they live, work, and play. Through looking at shoes, the reader travels to every era in time and all over the world. Interesting facts are shared in the divisions of protection, authority, status, fashion, magic, life's milestones, and play. Some bits of trivia included are the following: Eskimo women living on the arctic coast west of Greenland carried their babies naked in their massive reindeer-skin boots. The patterns on the soles of Egyptian sandals left messages for others. Professional ballerinas may wear out sixty-five pairs of toe shoes in one month. Wealthy people had their servants “break in” their new shoes by wearing them for six months so that they would be comfortable. Thomas Jefferson was the first president to wear oxford shoes with shoelaces. At the time it created quite a controversy. Because he was flat-footed and slightly pigeon-toed, President Lincoln found boots uncomfortable and instead wore carpet slippers around the White House. One legend says that the practice of binding feet by Chinese women was started by an Emperor whose daughter was born with deformed feet. He didn't want the future Empress to be embarrassed, so he announced that only women with very small feet could be considered truly feminine and desirable. The eight-page bibliography gives the reader confidence in the thorough research done for this book. There are 82 superb photographs which allow the reader to see extravagant as well as essential shoes. The book is interesting and well written. The novelty of the topic is certain to draw both young and old readers. It is a must-have for a public or school library. x, 132 p. : ill. 24 cm. Children's Book and Play Review, September / October 1997